2012
DOI: 10.1111/jph.12008
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Yield Losses Due to Anthracnose Stalk Rot on Corn in Brazilian Conditions

Abstract: The anthracnose stalk rot of corn (ASR), caused by Colletotrichum graminicola, is a major disease of this crop and occurs in most Brazilian regions where corn is grown. Despite its widespread occurrence, there are no estimates of the effect of ASR on the yield of corn under the Brazilian conditions. In this study, we evaluated the effect of ASR on corn hybrids yield. Two experiments were conducted (first crop 2007/2008 and second crop, 2009) in areas with a history of occurrence of leaf anthracnose and ASR. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
1
22
0
2
Order By: Relevance
“…Wils é uma das doenças mais importantes na cultura do milho em vários países, causando acamamento das plantas, redução na produção e qualidade dos grãos (BERGSTROM & NICHOLSON, 1999;COTA et al, 2012;MATIELLO et al, 2013). Os sintomas da antracnose do colmo são mais visíveis após o florescimento das plantas de milho, porém o processo infeccioso inicia-se pelos propágulos provenientes das lesões foliares ou daqueles presentes em restos culturais.…”
Section: Introductionunclassified
“…Wils é uma das doenças mais importantes na cultura do milho em vários países, causando acamamento das plantas, redução na produção e qualidade dos grãos (BERGSTROM & NICHOLSON, 1999;COTA et al, 2012;MATIELLO et al, 2013). Os sintomas da antracnose do colmo são mais visíveis após o florescimento das plantas de milho, porém o processo infeccioso inicia-se pelos propágulos provenientes das lesões foliares ou daqueles presentes em restos culturais.…”
Section: Introductionunclassified
“…The red mark is a kind of background to resistance; though there are some red susceptible genotypes. The simple hybrid 2B710 has an effective resistance level and showed red pigmentation in the stalk surface and leaves veins, which appears in some genotypes due to the production of carotenoids and flavonoids (GARDINGO, 2008;COSTA et al, 2010b;COTA et al, 2010;COTA et al, 2012;CARVALHO et al, 2013). This genotype has been used as a positive control in studies investigating anthracnose stalk rot resistance, as well as for genotype selection in germplasm banks; in addition, this hybrid has shown good agronomic features in many studies (COTA et al, 2012;CARVALHO et al, 2013;ZUCARELI et al, 2013, COSTA et al, 2014.…”
Section: Resultsmentioning
confidence: 99%
“…It is the principal disease of maize, capable of causing plant lodging, early plant death, and losses of approximately 35% in grain weight (BERGSTROM & NICHOLSON, 1999;DENTI & REIS, 2003;PALAVERSIC et al, 2009;COSTA et al, 2010a;JIRAK-PETERSON & ESKER, 2011;COTA et al, 2012 have a wet aspect and are brown to reddish in color, while old lesions are typically dark brown to black in color. In the stalk tissues, it is possible to see typical dark-brown coloring, which corresponds to necrotic lesions that lead to plant lodging and early death (BERGSTROM & NICHOLSON, 1999;COTA et al, 2012). This disease is one of the most important in maize crops and is very hard to control necessitating the use of integrated management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Nicholson 1999; Costa et al 2010aCosta et al , 2014Cota et al 2012). In addition to cultural methods, studies have reported the potential to use host plant resistance to manage ALB or ASR (Badu-Apraku et al 1987;Toman and White 1993;Coêlho et al 2001;Palaversic et al 2009;Frey et al 2011;Chung et al 2011;Matiello et al 2012).…”
mentioning
confidence: 99%
“…Each experiment used twenty C. graminicola isolates, and was defined by a single commercial hybrid varying in susceptibility to the anthracnoses. The hybrid BRS1010 is considered susceptible to anthracnose (Costa et al 2010b;Cota et al (Costa et al 2010b(Costa et al , 2014Cota et al 2010;Carvalho et al 2013), 2B707 is considered resistant to stalk disease, and P30F35 and P3862 are considered moderately resistant to stalk disease (Cruz et al 2013).…”
mentioning
confidence: 99%